2022
DOI: 10.1055/a-1865-1256
|View full text |Cite
|
Sign up to set email alerts
|

Behandlungsergebnisse in der Psychosomatischen Rehabilitation – Die Hersfelder Katamnesestudie

Abstract: Zusammenfassung Ziel der Studie Vorliegende Evaluationsstudien zeigen Verbesserungen im Verlauf und nach der Behandlung in Psychosomatischen Rehabilitationskliniken. Doch die Kliniken sehen sich neuen Herausforderungen gegenüber, die beispielsweise auf die Veränderungen in der Arbeitswelt zurückzuführen sind. Gleichzeitig treten neue Patientengruppen, wie u. a. ältere Patient*innen, mehr in den Fokus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(43 reference statements)
0
2
0
3
Order By: Relevance
“…Besonders die Begegnungen mit Mitpatienten können zur Verbesserung der fremdbezogenen Mentalisierungsfähigkeit beitragen 32 . Dass auf der Basis dieser in der modernen psychodynamischen Psychotherapie formulierten Konzepte konstruktive therapeutische Prozesse angestoßen und Behandlungsergebnisse erzielt werden können, deren Effektstärken sich nicht von denen jüngerer Patienten unterscheiden, konnte in der Hersfelder Katamnesestudie gezeigt werden 33 .…”
Section: Diskussionunclassified
“…Besonders die Begegnungen mit Mitpatienten können zur Verbesserung der fremdbezogenen Mentalisierungsfähigkeit beitragen 32 . Dass auf der Basis dieser in der modernen psychodynamischen Psychotherapie formulierten Konzepte konstruktive therapeutische Prozesse angestoßen und Behandlungsergebnisse erzielt werden können, deren Effektstärken sich nicht von denen jüngerer Patienten unterscheiden, konnte in der Hersfelder Katamnesestudie gezeigt werden 33 .…”
Section: Diskussionunclassified
“…Nevertheless, since the data were assessed in clinical routine without a narrow selection of patients, we consider the results of our study to be representative of patients in inpatient rehabilitation treatments. This is further underscored by the similarity of results compared to other studies in the psychosomatic rehabilitation setting [47]. Additionally, a recent study has shown that therapy outcomes in the psychosomatic rehabilitation setting based on real-world data collected from relatively unselected samples during clinical routine may substantially differ from laboratory randomized controlled trials [48] and thus highlight the importance of observational real-world outcome studies.…”
Section: Strength and Limitationsmentioning
confidence: 88%
“…Inpatient treatment in a psychosomatic clinic offers a particularly suitable treatment setting for this (Peters, 2021c), among other things, because social skills can be strengthened in the therapeutic community and thus social activities can be expanded in the long-term. In the Hersfelder-Katamnese-Studie, it became clear that older patients benefit from treatment just as much as younger patients (Peters et al, in press).…”
Section: Discussionmentioning
confidence: 99%